Sport as political agent in Cold War's dynamics: GDR's athletes in the National Autonomous University of Mexico, 1976-1979 - Omar Gerardo Chanocua Gómez; Andrea Torrealba Torre (Universidad Politécnica de Madrid, 2024)
The purpose of this article is to explain the visit of two delegations of German Democratic Rrepublic's athtletes to the National University Autonomous of Mexico and Jalisco state between 1978 and 1979. The aim of this article is to study university sports, its scope and limitations, from a different perspective, as well as to think of them as a device for international and diplomatic relations, symbolically important in the dynamics of the Cold War. Using the methodology of sports history, supported by reflections on new actors that break the dichotomy supposedly prevailing during the bipolar conflict, allows us to think about the power of sport as an international political agent, as well as to open paths of discussion and analysis yet to be written. In conclusion, thinking about the history of university sport from its relational character leads us to question traditional ideas about sports competitions, their spaces and actors, as well as their importance in international relations.